Integrated Management of Water Hyacinth as Alternative Renewable Energy Through Community Involvement along the Shores of Lake Victoria Kenya - Odero, Martin Omondi (JOOUST, 2015)
All over the world water hyacinth has remained a serious challenge wherever it has proliferated. The objectives of the study were to: compare calorific value of water hyacinth dry matter with those of local wood fuels; assess the difference between men and women in their awareness of water hyacinth as an alternative source of renewable energy; investigate the perception of individuals on water hyacinth as a source of alternative renewable energy across the three zones; and determine the levels of community involvement in water hyacinth control across the zones. The Systems Theory was used to study the interrelation among the various variables in the study which was carried out along the beaches of Lake Victoria in Kisumu and Homa Bay counties. Water hyacinth was harvested, chopped, dried, carbonized and compressed in an extrusion system. Eight hyacinth briquettes and eight carbonized wood samples were tested for calorific values using Isoperibol 1266 Bomb Calorimeter. The fishing community in the study area belonging to a beach management unit was the study target. Survey was used through focus group discussions. Systematic random sampling was applied to sample 18 beaches and 152 respondents in the study region. t-test indicated that the calorific value of water hyacinth briquettes was statistically different from those of local plant fuels, with local woods being higher, though, decision by the community to use any biomass as fuel depends on its abundance and not on cost or calorific value. t-test was applied to determine the variation of awareness of water hyacinth as an alternative renewable energy with gender and showed that there is no significant difference between the awareness of men and women on water hyacinth as an alternative renewable energy. The ANOV A test on comparison of perception of individuals across the zones provided F = 2.426 with 2 and 149 degrees of freedom with p-value (Sig.)= 0.092 > 0.05 revealed that, perception differed by the zone of residence. The study recommends that heavy duty briquette presses to improve quality of briquettes be made and placed in the hands of trained beach community members. These should be put in the hands of the community after their capacity building.